FLYPAPER EFFECT PADA DAU DAK DAN PAD TERHADAP BELANJA DAERAH PROVINSI JAWA TIMUR - Asriati, Dona; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to provide empirical evidence to the influence of general allocation fund, specialallocation fund, and local own source revenue to the local government expenditure of districts/cities in East Javaprovince and to provide empirical evidence to the tendency of the occurrence of flypaper effect on the influence ofthe general allocation fund to the local expenditure is greater than the influence of local own source revenue tothe local government expenditure of districts/cities in Indonesia. This research has been done by usingquantitative research and causality method. The population is all districts and cities in East Java Province i.e. 38areas with the observation periods from 2011 to 2015 and the sample collection technique has been conducted byusing purposive sampling. The data analysis technique has been carried out by using multiple linear regressions.Based on the result of the hypothesis test it can be concluded that: 1) local own source revenue (PAD) givespositive influence to the local expenditure. 2) General allocation fund (DAU) gives positive and significantinfluence to the local expenditure. 3) Special allocation fund (DAK) gives significant and positive influence tothe local expenditure. 4) The coefficient value of the General Allocation Fund is greater than coefficient value ofLocal Own Source Revenue, it shows that the flypaper effect has occurred in local expenditure of cities/districtsin East Java Province.Keywords: PAD, DAU, DAK, local expenditure, flypaper effect.